Evaluation Of Land Suitability For Oil Palm (Elaeis Quineensis Jacq.) In Lubuk Karak Village Sembilan Koto District Dharmasraya - Darwin Lumban Gaol; Edwin; Dewi Rezki (Jurusan Budidaya Perkebunan, 2023)
Currently, the government continues to encourage the development of oil palm plantation areas with the aim of boosting domestic economic activity. Nagari Lubuk Karak has a large area of land and has the potential to be developed into plantations, especially oil palm plantations. This regency has a land area of 1056 ha. Therefore, an evaluation of land suitability needs to be carried out in order to know the actual and potential land suitability class recommendations for oil palm plantations in that village. The stages in the research included secondary data collection, pre-survey, main survey and soil analysis in the laboratory. Land suitability classification is done by matching method. From the research results it is known that the limiting factors in the actual land suitability class at the study site were temperature, water availability, nutrient retention, and erosion hazard. After improvements have been made with good land management, the land suitability class can be increased with a potential land suitability class, which was previously classified as S3, increased to S2, and previously classified as S2, can be increased to S1. Thus, to obtain good oil palm growth in this region, it is necessary to improve the limiting factors on each land.